Impact of urbanization on ecological efficiency in China: An empirical analysis based on provincial panel data. (October 2021) - Yao, Jiadai; Xu, Pengpeng; Huang, Zhijin
Graphical abstract: Abstract: Urbanization is a complex economic and social phenomenon. Recently, rapid urbanization has not only caused rapid economic development in China, it has also posed a major threat to the ecological environment. Therefore, this study aims to determine how urbanization and its internal structure affect ecological efficiency (eco-efficiency) using panel data from China's 30 provinces from 2008 to 2017. First, the eco-efficiencies of 30 provinces in China were calculated using the super slack-based measure model (super-SBM model). Then, the entropy method was used to measure the comprehensive level of urbanization from different dimensions. Finally, the Spatial Durbin model was used to analyze the impact mechanisms of urbanization dimensions and the internal structure effect of each dimension on eco-efficiency. The results show that, from 2008 to 2017, the comprehensive level of China's urbanization in each dimension showed an upward trend, while the average eco-efficiency declined slightly. Further, local eco-efficiency exhibited a negative spatial effect on the surrounding areas. In particular, the local social urbanization level inhibited the eco-efficiency of the surrounding areas, while the local population urbanization level promoted the eco-efficiency of the surrounding areas. Moreover, population and ecological urbanization had significant positive impacts on local eco-efficiency, while social and spatial urbanization had significant negative impacts.